Defining the food safety landscape in Cambodia: the ecology of Salmonella enterica in informal markets - Schwan, Carla Luisa (Kansas State University, 2020)
The lack of hygiene and sanitation practices and insufficient infrastructure in Cambodian informal markets may increase the risk of food contamination, specifically raw vegetables, which in turn may increase the chances of contracting a foodborne disease. The aims of this research were i) to quantify the prevalence of Salmonella enterica based upon seasonal differences (rainy and dry) between surface types (food contact surface [FCS] and non-food contact surface [NFCS]) and between location of vendors within the market (inside and outside), ii) to characterize Salmonella enterica serotypes abundance, and iii) identify and characterize the genotypic antimicrobial resistance profiles of Salmonella enterica strains isolated from environmental samples in informal markets in Cambodia. A total of 310 samples were screened for Salmonella enterica prevalence following the U.S. Department of Agriculture guidelines and confirmed by PCR. Whole Genome Sequencing was performed and the serotype for each isolate was determined in-silico using SeqSero 1.0 on draft genomes. Antimicrobial resistance (AMR), stress and virulence genotypes were retrieved from the National Center for Biotechnology Information (NCBI) Pathogen Detection engine. Salmonella enterica pathogenicity islands (SPIs) were identified with SPIFinder (Center for Genomic Epidemiology). A total of 81 samples were confirmed positive for Salmonella enterica. During the dry season, Salmonella enterica was more prevalent on FCS compared to NFCS (estimated probability of detection [confidence interval]: 0.41 [0.25,0.59] and 0.17 [0.08, 0.32], respectively; P=0.002), though no differences were apparent during the rainy season. Further, there was no evidence of any differences in Salmonella enterica prevalence based on location within the market (P=0.61). Sixteen Salmonella enterica serotypes were detected across multiple surfaces, Rissen (n=19); Hvittingfoss (n=13); Corvallis (n=10); Krefeld (n=8); Weltevreden (n=6); Altona (n=6); Mbandaka (n=5); Typhimurium (n=3); Javiana, Uganda, and Derby (n=2 each); Anatum, Braenderup, Lexington, Virchow, and the potential monophasic variant of S. enterica serotype Typhimurium (I 4,[5],12:i:-) (n=1 each). AMR genes were identified in 43 out of 81 strains, including those encoding tetracycline, beta-lactam, sulfonamide, quinolone, aminoglycoside, phenicol, trimethoprim, and fosfomycin resistance. A total of 10 SPIs (SP1, 3-5, 8, 9, 12-14, centisome 63) were detected in 59 genomes. SPI-1, SPI-4 and SPI-9 were present in 13%, 2%, and 5% of the isolates, respectively. The availability of robust and accurate data on the ecology of Salmonella enterica in these markets is crucial for active surveillance, implementation of suitable intervention strategies, and prevention of domestic foodborne illness cases. These studies may serve as guiding references to develop further food safety research, education and intervention programs, and even policy drafting. They will support decision making within the Ministry of Health and the Ministry of Agriculture, Forestry, and Fisheries in Cambodia and foster public health protection, as well as support global epidemiological investigations of outbreaks.
Keywords: Food safety; Informal markets; Cambodia; Salmonella enterica; Antimicrobial resistance